POTENTIAL DECREASE GLASS GAS EMISSION THROUGH MATERIAL CONVERSION FUEL GAS ON GENERAL PUBLIC VEHICLE - Zainal Arifin (Jurnal Penelitian Saintek, 2014)
The objective of the research is to retrofit city buses with fuel gas (LPG) is it also gives a general recommendation implementation of control schemes in Indonesia and foundation policies investment, especially urban transportation sector by using the control scheme , in addition to develop the methodology for the valuation of the environmental improvement of urban transport investment. This research can be used for decision-makers for national and local level (city government) in developing policies, strategies, and urban transportation investment program. The results show that the fuel consumption per day are 28.544kg 35.68 liters of diesel (diesel density of 0.8kg/l) and lower heating value of 42.5 MJ/kg, the energy used at 1213.12 MJ/days. The level of reduction in Greenhouse Gas Emissions (GHG) per year to replace petroleum diesel with LPG at 111.93 tons, the total GHG emission reduction of 11 081 tonnes of CO2 e. Financial benefits of LPG generates NPV of Rp. 18,518,582; if there is a rise in the price of LPG fuel, resulting NPV of (-) Rs. 58.17.169. NPV indicates a positive result for Rp. 100 051 666 if bus fares increased 25% from the current rate